Halogen-bonded cocrystals of donepezil with perfluorinated diiodobenzenes. Issue 34 (14th August 2020) - Nemec, Vinko; Vitasović, Toni; Cinčić, Dominik
Abstract : Donepezil, an active pharmaceutical ingredient with several different acceptor sites for halogen bonding has successfully been cocrystallized with two perfluorinated halogen bond donors. Abstract : Donepezil, an active pharmaceutical ingredient with several different acceptor sites for halogen bonding has successfully been cocrystallized with two perfluorinated halogen bond donors. The prepared cocrystals provide insight into the halogen bonding potential of organic molecules with increased structural complexity.